The effects of household water, sanitation, and hygiene on early childhood education enrollment: evidence from the 2022 Bangladesh demographic and health survey - Ashraful Alam; Md. Emon Prodhan; Faizul Islam; Mohammad Nayeem Hasan; Muhammad Abdul Baker Chowdhury; Md Jamal Uddin (BMC Public Health)
Abstract Background Effective early childhood education (ECE) programs, including elementary schools, kindergartens, and daycare facilities, are instrumental in fostering cognitive, social, emotional, and motor development. Access to water, sanitation, and hygiene (WASH) facilities, as mandated by Sustainable Development Goals (SDGs) 6, is integral in bolstering health and enhancing educational engagement globally. This study examines the impact of WASH facilities and sociodemographic factors on ECE enrollment in Bangladesh. Methods Data were extracted from the 2022 Bangladesh Demographic and Health Survey (BDHS), on which 2494 children’s information and socioeconomic characteristics were analyzed. The outcome variable was ECE enrollment, and the exposure variable was WASH facilities—defined as having an improved water source, an improved nonshared toilet, and a basic handwashing facility—at the household level. Crude and adjusted logistic regression models were applied to determine significant associations between ECE enrollment and WASH facilities, including other covariates. Results Children from households with basic handwashing facilities presented greater odds of ECE enrollment (AOR = 1.33, 95% CI 1.00–1.76, p value = 0.043), whereas improved toilet facilities were correlated with a greater chance of participation (AOR = 1.24, 95% CI 0.97–1.59, p value = 0.085). Treating drinking water significantly increased the probability of enrollment (AOR = 1.55, 95% CI 1.15–2.90, p value = 0.004). Regional disparities were mentionable; children in Rangpur (AOR = 1.94, 95% CI 1.33–2.81, p value = 0.001), Rajshahi (AOR = 1.47, 95% CI 1.01–2.13, p value = 0.043), Mymensingh (AOR = 1.39, 95% CI 0.97–1.99, p value = 0.096), and Khulna (AOR = 1.34, 95% CI 0.93–1.94, p value = 0.116) had higher odds of enrollment than Barishal did. Mothers’ education is also a key determinant; children of mothers with secondary education were 40% more likely to enroll (AOR = 1.40, 95% CI 1.00–1.96, p value = 0.049), and those with higher-educated mothers exhibited a similar trend (AOR = 1.43, 95% CI 0.95–2.16, p value = 0.088) compared with children of mothers with no education. Conclusions Our findings highlight the significance of household access to water, sanitation, and hygiene (WASH) facilities in early childhood education enrollment in Bangladesh. To advance progress toward SDGs 4 (quality education) and 6 (clean water and sanitation), policymakers should prioritize well-established WASH facilities, maternal education programs, and region-specific strategies.